The feasibility of in vivo quantification of bone-gadolinium in humans by prompt gamma neutron activation analysis (PGNAA) following gadolinium-based contrast-enhanced MRI. (November 2015) - Mostafaei, F.; McNeill, F.E.; Chettle, D.R.; Noseworthy, M.D.; Prestwich, W.V.
Abstract: The feasibility of using a 238 Pu/Be-based in vivo prompt γ-ray neutron activation analysis (IVNAA) system, previously successfully used for measurements of muscle, for the detection of gadolinium (Gd) in bone was presented. Gd is extensively used in contrast agents in MR imaging. We present phantom measurement data for the measurement of Gd in the tibia. Gd has seven naturally occurring isotopes, of which two have extremely large neutron capture cross sections; 155 Gd (14.8% natural abundance (NA), σ = 60, 900 barns) and 157 Gd (15.65% NA, σ = 254, 000 barns). Our previous work focused on muscle but this only informs about the short term kinetics of Gd. We studied the possibility of measuring bone, as it may be a long term storage site for Gd. A human simulating bone phantom set was developed. The phantoms were doped with seven concentrations of Gd of concentrations 0.0, 25, 50, 75, 100, 120 and 150 ppm. Additional elements important for neutron activation analysis, Na, Cl and Ca, were also included to create an overall elemental composition consistent with Reference Man. The overall conclusion is that the potential application of this Pu–Be-based prompt in vivo NAA for the monitoring of the storage and retention of Gd in bone is not feasible. Highlights: The feasibility of using a 238 Pu/Be based prompt in vivo neutron activation analysis (IVNAA) system for measuring Gd in bone was investigated. The observed detection limit was poor: approximately 150 ppm. We verified the poor detection limit using an alternative method in the McMaster Nuclear Reactor (MNR). We compared the performance of this prompt gamma neutron activation analysis (PGNAA) system against an XRF system. Our conclusion is that this particular system is not suited to detection of Gd in bone.